Sea ice draft from upward-looking Acoustic Doppler Current Profilers (ADCPs): an adaptive approach, validated by Upward-Looking Sonar (ULS) data. - Belter, Hans Jakob; Janout, Markus; Krumpen, Thomas; Ross, E; Hölemann, Jens A; Timokhov, Leonid; Novikhin, Andrey; Kassens, Heidemarie; Wyatt, G; Rousseau, S; Sadowy, D (PANGAEA, 2019)
Within the framework of the Russian-German BMBF-funded TRANSDRIFT project moored Upward-Looking Sonars (ULSs) were deployed in the Laptev Sea between 2013 and 2015. Two ULS of the type Ice Profiling Sonar 5 (420 kHz, manufactured by ASL Environmental Sciences) were deployed at the 1893 and Taymyr stations in September 2013. During a Russian expedition in September 2014 both moorings were recovered and redeployed at the two station until September 2015. The four labels (ULS_1893_1314, ULS_Taymyr_1314, ULS_1893_1415 and ULS_Taymyr_1415) are named to indicate the Location of the deployment (station name) and the sampling period. Each dataset contains values of daily averaged sea ice draft (in m). The deployment sheets are attached as well.
Daily mean sea ice draft from moored Upward-Looking Sonars in the Laptev Sea between 2013 and 2015
Keywords: AWI_SeaIce; Laptev Sea; Laptev Sea System; LSS; sea ice draft; Sea Ice Physics @ AWI; ULS